Konsentrasi Hambat Minimum dan Konsentrasi Bunuh Minimum Ekstrak dan Nanopartikel Ekstrak Etanol Daun Pepaya (Carica papaya L.) Terhadap Candida albicans - Nurmala, Syandoval Triska Ananda; Rahayu , Yayuk Putri; Pulungan, Ainil Fithri; Miswanda, Dikki (Journal of Pharmaceutical and Sciences, 2025)
Background: Fungal infections, particularly those caused by Candida albicans, are a significant health problem in tropical countries such as Indonesia. Humid environmental conditions, inadequate sanitation, high population density, and low socioeconomic levels contribute to the high prevalence of fungal infections. Papaya leaves (Carica papaya L.) are known to contain bioactive compounds with antifungal potential; however, their effectiveness can be enhanced through nanoparticle formulation. Objective: This study aimed to formulate nanoparticles of ethanol extract from papaya leaves and evaluate their antifungal activity against Candida albicans by comparing the Minimum Inhibitory Concentration (MIC) and Minimum Fungicidal Concentration (MFC) values between the conventional extract and the nanoparticle extract. Methods: This experimental study utilized ethanol extract of papaya leaves and its nanoparticle formulation at varying concentrations. Particle size was characterized using a Particle Size Analyzer (PSA). Antifungal activity was tested against Candida albicans ATCC 10231 using broth and agar dilution methods as well as the disk diffusion method. Data were statistically analyzed using one-way ANOVA. Results: The nanoparticle extract exhibited a smaller particle size (330.27 nm) compared to the conventional extract (2203.45 nm). The MIC of the nanoparticle extract (1.25%) was lower than that of the conventional extract (12.5%), while the MFC of the nanoparticle extract (5%) was equivalent to that of the conventional extract (50%). The disk diffusion test showed that the 5% nanoparticle extract had an inhibition zone of 21.6 mm, classified as sensitive and comparable to the 50% conventional extract. Conclusion: The nanoparticle formulation of papaya leaf extract enhanced antifungal efficacy, enabling a tenfold dose reduction compared to the conventional extract. These findings highlight the potential of nanoparticles as a more efficient alternative therapy for fungal infections.